Role of Li+ ion in the luminescence enhancement of lanthanide ions: Favorable modifications in host matrices - Singh A.K.; Singh S.K.; Rai S.B. (My University, 2025)
Lanthanide based materials are preferred over other luminescent materials for various applications. Current focus in this area is to exploit the unique luminescence features of lanthanide-based materials for multidisciplinary research and novel applications. Furthermore, efforts are going on to enhance the luminescence of lanthanide ions for better performance. In a broader sense, there are two ways to enhance the luminescence of lanthanide ions. The first is to use a suitable sensitizer, which can absorb excitation energy efficiently, and can transfer it to the lanthanide ions. This method has been known for a long time and is well documented in the literature. The second way is to modify host matrices in such a way that it favors radiative transitions. It is widely reported in the literature that the presence of alkali ions, particularly Li+ ions, in a matrix enhances the luminescence of lanthanide ions significantly. But there are no comprehensive reports available in the literature that summarize how alkali ions help in the luminescence enhancement of lanthanide ions in various host matrices. The prime objective of this review is to highlight various contributing factors that help in the luminescence enhancement of lanthanide ions in the presence of alkali ions. This journal is © the Partner Organisations 2014.